Bevacizumab-induced dysphonia: A case report with brief review of literature. (June 2020) - Lam, So Yi; Lee, Chung-Shien; Sharma, Sandhya; Cheng, Kit
Introduction: Anti-angiogenic treatment in adjunct with chemotherapy is widely used for the treatment of various cancers. These agents inhibit vascular endothelial growth factor (VEGF) signaling thereby inhibiting tumor proliferation and invasion. Dysphonia, or voice changes, has been documented, but is an underreported side effect of anti-angiogenic agents. We report a case of intermittent dysphonia in a patient with metastatic, platinum-refractory ovarian cancer treated with bevacizumab. Case report: A 48-year-old female with high grade mixed type ovarian adenocarcinoma and concurrent left sided breast cancer was transitioned to palliative therapy with gemcitabine-bevacizumab for her ovarian cancer. At a follow-up visit after three cycles of the new therapy, the patient complained of intermittent changes in her voice, describing periods of hoarseness or softness in her voice after the chemotherapy—sometimes to the point that her voice was inaudible. Management and outcome: A new pelvic thrombus was discovered upon assessment of the patient's disease. Bevacizumab was held and she was referred to ear, nose, and throat evaluation for dysphonia. Laryngoscopic examination showed normal vocal cord, with normal movements and no lesion or necrosis. During subsequent follow-up, the patient reported improvement in her voice with no additional dysphonia. Discussion: Vocal adverse effects of anti-VEGF agents have been documented in landmark trials and case reports; however, clinicians are often unaware of this rare side effect. Although VEGF-induced dysphonia may be rare and may not impede the patient's quality of life in some cases, it is critical to acknowledge and not underestimate this adverse effect.